A Fistful of NIL: Have We Entered a “Wild West” Recruiting Era? - Marshall Magnusen; Samuel Y Todd (Journal of Applied Sports Management, 2021)
Changes about the National Collegiate Athletic Association’s (NCAA) Name, Image, and Likeness (NIL) policy impacted the world of college sports in the summer of 2021. Emerging from the dust of this seismic event was an apparent new frontier for athletes, coaches, and universities to explore. In the eyes of many, college sports had now entered a “Wild West” frontier because of NIL, especially as it pertains to recruiting athletes. But what does that really mean, “Wild West”? And further, if such a comparison is at least somewhat accurate, are there lessons that can be learned from other sectors who likewise experienced supposed western-like eras? The purpose of this article is to address these two pressing questions.
Keywords: College Sports; Governance; NCAA; Recruiting; Sponsorship; Student-Athletes